THE ACCOUNTING CURRICULUM AND POSTGRADUATE ACHIEVEMENT. - Anderson, Hershel M.; Griffin, Fred B. (The Accounting Review, 1963)
The article presents information on accounting curriculum. In the past several years, reform of the collegiate curriculum in business administration has developed into a modern Crusade. The acknowledged enemy is stultifying specialization; the sanctioned goal, a liberal education. Unfortunately, as in most such movements, the participants have often disagreed over just what or who the enemy is, as well as the shortest and safest route to the objective, which is only vaguely defined. As a result, more than a little confusion has attended our deliberations on a worth-while cause. Due to the necessary lack of precision in the sciences dealing with human conduct, an inductive, empirical approach to the problem is impossible. Instead, proposals for changing the old order have had to make the best of fragmentary factual data and theories from educational psychology. In a few cases ethical considerations have been introduced, despite the extreme hazards involved. The arguments of the innovators often fail to carry their conclusions. Only time can finally clarify all the issues involved and judge the adequacy and wisdom of the many changes which have been frequently proposed and occasionally adopted.